Pertumbuhan dan perkembangan larva Musca domestica Linnaeus (Diptera: Muscidae) dalam beberapa jenis kotoran ternak - Ramadhani Eka Putra; Abdul Rosyad; Ida Kinasih (Jurnal Entomologi Indonesia, 2013)
House fly (Musca domestica) is an important urban insect that can transmit various infectious diseases. This insect usually utilized organic wastes as nutrition source for their larvae. One of the main sources of organic wastes is livestock manure produced by animal farming located near human dwelling area. Thus, appropriate house fly population control program at animal farm is needed,based on information on the house fly’s life history. The research is focused on the development of house fly larvae reared with different livestock manures, such as cow, chicken, and horse. As comparison, rice bran were used as control. Results showed that larvae reared with horse manure has the shortest development time (5 days), with lowest larval survival rate (30%), pupal weight (6.8 ± 0.141 g), and weight of female imago (4.9 ± 0.14 g). This finding indicates the lowest nutrition value of horse manure for house flies larvae. Further research is needed to find the effect of manure to variables that directly influence population growth, such as fecundity of female flies and egg survivorship. These additional information on life history will help the design of appropriate house fly population management program for animal farm.